Pierzchliwa, młoda, płocha — wizerunek głównej bohaterki romansu Samuela Twardowskiego ze Skrzypny Nadobna Paskwalina w kontekście mitologii - Sadowski, Michał (Starość i młodość w literaturze i kulturze, 2016)
The article is about a motif of youth, uncertainty and attempts to find each other through the journey.The romance of Twardowski contains a lot of interesting silhouette forms, which has been embroiled ina conflict of life, especially the title character. Referring primarily to mythology, except for Paskwalina, willbe subject for the characteristics also other characters of the work, including, among others the opponentof Paskwalina — Venus.